Reproductive decisions among couples with HIV/AIDS in Zimbabwe: a descriptive qualitative study of a sample from Bulawayo - Ndlovu, Vezumuzi (Department of Sociology, 2014)
Men and woman of reproductive age are the largest group infected with the human immunodeﬁciency virus (HIV) in Zimbabwe. Over 70% of the reported HIV/AIDS cases in Zimbabwe are among the 20-29 year age group. The purpose of this exploratory study was to explore and describe the impact of being HIV positive on the reproductive and sexual choices or decisions made by HIV positive couples given that in Zimbabwean society it is generally expected that couples, especially married ones, should reproduce. The study explored the context of decision making, the content of decisions made, the process of making those decisions as well as the actors involved in the decision making process. In pursuance of the purpose of the study, the socio-cultural context which determines the value framework within which HIV positive couples live and make their decisions was explored as was the economic as well as the medical context. The study also examined the role of health professionals and the family on the reproductive decisions made by HIV positive couples. The gender based power dynamics within the relationships of the positive couples was also given due attention. Having explored these factors the study found that being HIV positive has both direct and indirect effects on the reproductive and sexual lives of HIV positive couples as well as on the decisions that they make. Several approaches were used to explore the impact of being HIV positive on reproductive decision making and how reproductive decisions and sexual choices were made by HIV positive couples within the context of the Zimbabwean patriarchal society. Includes bibliographical references (p. 161-178).